How to Start a Rebellion: Using Film to Engage Social Studies Students - Jones, Ariel (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
History teachers face the obstacle of connecting content about the past to their students living in the present. Research in the fields of film, psychology, and education suggest that the use of narrative film in the social studies classroom actually more effectively engages students in the class itself, as well as the historical material. When they are more engaged, they grow cognitively, as well as in terms of their meaningful learning and preparation to become citizens of our society. This article explores the views of experts in these fields, as well as the implementation of film as a teaching tool in an urban high school history class.